The Influence Of Effective Communication, Supervision Of The Head Of The Room, And Documentation Of Nursing Care On Improving Patient Safety In Inpatient Rooms (Systematic Literature Reviews) - Dian Tri Febriana; Achmad Zakaria; Adhitya Chandra Setyawan; Muhammad Zulfikar Asumta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify and analyze the influence of effective communication, head nurse supervision, and nursing care documentation on improving patient safety in inpatient rooms through a systematic literature review. Materials and methods. This research used the Systematic Literature Review (SLR) method to evaluate how effective communication, head nurse supervision, and accurate nursing documentation contribute to patient safety. Literature was obtained from international databases such as PubMed, ScienceDirect, Scopus, ProQuest, and Google Scholar, covering publications from 2018 to 2024. The article selection process followed a systematic screening of titles, abstracts, full texts, and quality assessment using the Joanna Briggs Institute (JBI) appraisal tools. Data were narratively synthesized under three main themes and adhered to ethical scientific principles, although no direct human subjects were involved. Results.The findings show that effective communication, accurate nursing documentation, and consistent supervision from head nurses significantly enhance patient safety in inpatient settings. Clear, structured, and empathetic communication fosters teamwork and improves clinical decision-making. Proper documentation supports continuity of care and minimizes medical errors. Supervision by the head nurse ensures procedural compliance and improves the overall quality of nursing services. Conclusions.Effective communication, accurate documentation, and proactive supervision are critical components in establishing a safe and high-quality inpatient care environment. Addressing barriers such as hierarchical culture and lack of training is essential for optimizing patient outcomes and strengthening healthcare team performance.